EVENT MODALITY IN BALKAN TURKISH: FORMAL AND SEMANTIC VARIATION IN CONTACT: Part 1. Possibility and Necessity (Journal of Contemporary Philology, 2025)
The present article constitutes the first part of a two-part study on event modality in selected Turkish varieties of Kosovo, North Macedonia, Bulgaria, and Eastern Thrace (Turkey). The linguistic structures will be compared with corresponding expressions in Modern Standard Turkish and pre-modern Ottoman Turkish varieties. The study identifies both common features and differences among the Balkan Turkish varieties. Variation occurs in different slots within the investigated constructions and concerns lexical, semantic and morphosyntactic features, including complementation patterns, where both infinitive and subjunctive structures can be found. The linguistic variation is partly dialect-specific and distributed differently among the eastern and western dialects of Balkan Turkish, but intra-dialectal variation is also observed. It will be argued that while some processes that have led to the present situation in Balkan Turkish may be attributed to internal developments of inherited structures and to universal tendencies, impact of language contact has also contributed to the distribution of certain structures within the Turkish dialects of the Balkans.
Keywords: dialectology; semantics; morphosyntax; complementation patterns